LANGUAGES SIGNALING APPLICATIONS USING MICROSOFT VISUAL BASIC 6.0 - Harry Busura; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2008)
The growing world of computer technology so that all problems can be solved with a computer, one of which is to create "Application of Sign Language", where by this we can know and be able to have conversations with people who can not speak and the hearing less. This application is designed with the view that attention to simplicity in operation.